Risk Factor Analysis of Malaria Incidence in Mimika Baru District, Mimika Regency, Central Papua Province - Rewasan, Mariana; Grace Esther Caroline Korompis; Josef Sem Berth Tuda (LPPM Universitas Harapan Bangsa, 2024)
Malaria remains a global issue. Indonesia ranks second in the highest number of cases in Asia. Malaria risk factors include host characteristics (age, gender, education), behavior (habit of going out at night, habit of working at night, habit of sleeping outside at night) and environmental factors (mosquito netting, bed net use, insect repellent use). This study aims to analyze the risk factors for malaria in Mimika Baru District, Mimika Regency, Central Papua. This research uses a quantitative approach with a cross-sectional study conducted on Desember 2023. The sampling technique involved 320 respondents using cluster sampling and purposive sampling. Data were collected through questionnaires and analyzed using univariate, bivariate (chi-square and T test), and multivariate (multiple logistic regression) analysis with SPSS. Out of 320 respondents, 117 (36.6%) tested positive for malaria and 203 (63.4%) tested negative. There were associations between gender (p=0.005), education (p=0.023), nighttime outdoor habits (p=0.025), nighttime work habits (p=0.000), sleeping outdoors (p=0.023), mosquito netting installation (p=0.012), bed net use (p=0.000), and insect repellent use (p=0.014) with malaria incidence. Age was not associated (p=0.302). The dominant factor was nighttime work habits (p=0.000; OR=13.898; 95% CI=6.447-29.959). Gender and education were significantly associated with malaria incidence, while age was not. Nighttime outdoor habits, nighttime work habits, and sleeping outdoors, as well as environmental factors were also significantly associated with malaria incidence in Mimika Baru